A review on heme oxygenase-1 induction: is it a necessary evil - Waza, Ajaz Ahmad; Hamid, Zeenat; Ali, Sajad; Bhat, Shabir Ahmad; Bhat, Musadiq Ahmad (Inflammation research, 2018)
Heme oxygenase-1 (HO-1) is considered to be the main protein in diseases arising as a result of oxidative and inflammatory insults. Tremendous research has been carried out on HO-1 since years, pertaining its cytoprotective effect against oxidative injury and other cellular stresses. HO-1, by regulating intracellular levels of pro-oxidant heme, or by other benefits of its by-products such as carbon monoxide (CO) and biliverdin (BV) had become an important candidate protein to be up-regulated to combat diverse stressful events. Although the beneficial effects of HO-1 induction have been reported in a number of cells and tissues, a growing body of evidence indicates that this increased HO-1 expression may lead to the progression of several diseases such as neurodegeneration, carcinogenesis. But it is not clear, what accounts for the increased expression of HO-1 in cells and tissues. The observed friendly role of HO-1 in a wide range of stress conditions since times is now doubtful. Therefore, more studies are needed to elucidate the exact role of HO-1 in various stressful events. Being more concise, elucidating the effect of HO-1 up-regulation on critical genes involved in particular diseases such as cancer will help to a larger extent to comprehend the exact role of HO-1. This review will assist in understanding the dual role (protective and detrimental) of HO-1 and the signaling pathway involved and will help in unraveling the doubtful role of HO-1 induction.